URBAN MUSLIM PREFERENCES AND THE USE OF SHARIA MONETARY INSTRUMENTS: A CASE STUDY IN PEKALONGAN - Kurniawati, Fitri; Soemitra, Andri; Harahap, Isnaini; Khoiri Furqon, Imahda; Adnan Ahmed Usmani, Sheikh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2025)
This study explores urban Muslims’ preferences in Pekalongan for sharia monetary instruments—sukuk, mudharabah, and murabahah—focusing on their adoption in supporting MSMEs, particularly in the batik sector. Using a descriptive qualitative method with a phenomenological approach, it draws on OJK and BPS Pekalongan data alongside scholarly literature, but requires clearer justification for how these sources are integrated analytically. Findings highlight a preference for mudharabah and murabahah due to their alignment with Islamic ethical values and practical utility for MSMEs, while sukuk is underutilized due to its complexity and limited local relevance. Key drivers of adoption include strong Islamic identity, expanding sharia banking and fintech, and batik cooperatives, with barriers such as low sharia financial literacy (39.11%), regulatory gaps, and competition from conventional systems. The study proposes a Localized Islamic Financial Adoption Model inclusion framework combining maqasid al-shariah and diffusion of innovations theory, emphasizing cultural identity, literacy, and regulation. It recommends tailored financial education and local regulatory enhancements to strengthen Pekalongan’s sharia financial ecosystem, offering a model for other small Indonesian cities.